Unfairness in Society and Over Time: Understanding Possible Radicalization of People Protesting on Matters of Climate Change - Jansma, Amarins; van den Bos, Kees; de Graaf, Beatrice A. (Frontiers in Psychology, 2022)
In this manuscript, we introduce a theoretical model of climate radicalization that integrates social psychological theories of perceived unfairness with historical insights on radicalization to contribute to the knowledge of individuals’ processes of radicalization and non-radicalization in relation to climate change. We define climate radicalization as a process of growing willingness to pursue and/or support radical changes in society that are in conflict with or could pose a threat to the status quo or democratic legal order to reach climate goals. We describe how perceptions of unfairness can play a pivotal role in processes of climate change related radicalization. Without taking any position or judgment regarding climate concerns and associated actions, we suggest that although these behaviors drive many people to participate in peaceful climate protest, they may also lead others to radicalize into breaking the law to achieve their climate goals, possibly in violent ways. This process of climate radicalization, we argue, can be driven by people perceiving certain situations to be blatantly unfair. Specifically, we discuss how radical attitudes and behaviors can be products of perceived unfairness stemming from the past, the future, the immediate social environments of perceivers, as well as those that are spatially distant from them. We further argue that because radicalization processes are shaped by an interaction between individuals and movements, on the one hand, and societal actors and developments, on the other, they tend to develop in non-linear and dynamic ways. We therefore propose that climate radicalization is a (1) dynamic, contingent, and non-linear process, often of an escalating (and sometimes de-escalating) kind, (2) that develops over time, (3) through various interactions between individuals and their contexts, and (4) in which people and groups move back and forth from peaceful protest, through disobedient and unlawful methods, to violent actions. Implications, strengths, and limitations of our model are discussed.